Carotid Sheath Abscess Caused by a Tooth Decay Infection on the Opposite Side - F. Ruya Tuncturk; Lokman Uzun; M. Tayyar Kalcioglu; Oguz Kadir Egilmez; Emine Timurlenk; Muferet Erguven (Case Reports in Otolaryngology)
Deep neck infections are mortal diseases that need emergency treatment. It can occur at any age but usually in pediatric ages. In this report, a left cervical carotid space abscess of a pediatric patient was discussed. It was interesting that the only origin of the left carotid sheath abscess was right inferior first molar tooth decay. Right neck spaces were all clean. Patient had no immunosupression and also there were no congenital masses such as branchial cleft cysts, foreign bodies, or masses suspicious for malignancies in cervical ultrasound and MRI. We discussed this rare condition under the light of the literature.